THE CONCEPT OF AL-QURâAN ON TEACHER COMPETENCY (Thematic Analysis of Surah Al-Qalam Verses 1-4) - yan, Rusi (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
AbstractThis study aims to know about the competence of teachers, and what theconcept of the Qurâan about the competence of teachers in Surat Al-QalamVerses 1 - 4. This research is a library review (library research) which isqualitative descriptive, using documentation techniques in data collection.While the method of data analysis used is the tafsir maudluâiy method. Theresults show that: Firstly, the qualities that an educator must have are (a)zuhud not putting matter and teaching because of seeking Godâs mercy; (b) tocleanse his body, away from sin and guilt, to escape from great sin, ridicity, envy,hostility, strife and other disgraceful nature; (c) Ikhlas in the work; (d) forgiving;(e) loving his disciples just as he loved his own son; (f) knowing the studentâsnature; (g) mastering subjects; (h) have competence in the ways of teaching.Second, the competence that must be owned by the teacher according to theQurâan letter Al-Qalam verses 1-4 is to have the personality as exemplified bythe Prophet Muhammad SAW, master and utilize information technology andcommunications for self-development and science and have the ability paperfor the development of science and communication media with others.Â Keywords: Competence of teachers, Concepts of the Qurâan, Tafseer of al-Alaq